Penerapan Non Delay Schedule Dengan Mempertimbangkan Machine Availability Constraint untuk Meminimasi Makespan pada PT Autotech Perkasa Mandiri, Cikarang, Jawa Barat - Anastasia Lidya Maukar; Ineu Widaningsih Sosodoro; Stefanus Setiady (President University, 2020)
One of the efforts to increase production efficiency is by implementing the right scheduling. PT Autotech Perkasa Mandiri is the job shop production system. Currently implements a heuristic method with a priority dispatch rule, namely the Earliest Due Date (EDD). The EDD rule has the highest priority for the job with the earliest due date to be processed on a machine. This study is to purpose a more optimal scheduling by comparing the makespan of the current schedule with the proposed one. Previous research is the non delay schedule without considering machine availability constraints. In this study, machine availability constraints are taken into account, thus, they are more realistic when applied to the actual problem. The algorithm used is a non delay schedule with working time window (WT-NSA). Machine availability constraints that are taken into account are lunch-break hours (12: 00-13: 00) and shift changes (17: 00-08: 00). From the analysis, it is obtained that makespan from non delay schedule is 23 hours 6 minutes, while makespan from WT-NSA is 26 hours 6 minutes, and makespan from EDD schedule is 38 hours 54 minutes. Non-delay schedule has the smallest makespan, which is 23 hours 6 minutes, but WT-NSA is more realistic when applied to the real problem.